Roque J. Ferriols, S.J., Sulyap sa Aking Pinanggalingan. Ed. Leovino Ma. Garcia - Strebel, Wilhelm P.J. S. (Archīum Ateneo, 2024)
Roque J. Ferriols, S.J., Sulyap sa Aking Pinanggalingan. Ed. Leovino Ma. Garcia